Proximate and distal factors associated with the stall in the decline of adolescent pregnancy in Uganda - Catherine Mbabazi; Alexander Kintu; John Bosco Asiimwe; John S. Ssekamatte; Iqbal Shah; David Canning (BMC, 2021)
Abstract Background Adolescent pregnancy in Uganda declined from 31% in 2000-01 to 25% in 2006 but thereafter stalled at 25% from 2006 to 2016. This paper investigates the factors associated with the recent stall in the rate of decline of adolescent pregnancy in Uganda. Methods We used logistic regression models for 4 years (2000-01, 2006, 2011 and 2016) of data from the Uganda Demographic Health Survey to explore proximate and distal factors of adolescent pregnancy in Uganda. We carried out Blinder-Oaxaca decomposition models to explore the contributions of different factors in explaining the observed decline in adolescent pregnancy between 2001 and 2006, and the subsequent stall between 2006 and 2016. Results We found that marriage among women aged 15-19 years, and early sexual debut, were strongly associated with adolescent pregnancy. These declined substantially between 2000 and 01 and 2006, leading to a decline in adolescent pregnancy. Their decline was in turn associated with rising levels of female education and household wealth. After 2006, education levels and household wealth gains stalled, with associated stalls in the decline of marriage among women aged 15-19 years and sexual debut, and a stall in the decline of adolescent pregnancy. Conclusions The stall in the decline of adolescent pregnancies in Uganda was linked to a stall in the reduction of adolescent marriage, which in turn was associated with limited progress in female educational attainment between 2006 and 2016. We emphasize the need for a renewed focus on girl's education and poverty reduction to reduce adolescent pregnancy in Uganda and subsequently improve health outcomes for adolescent girls.